Ակ. Բակունցի «Մթնաձորի «չարքը»» պատմվածքի հոգեբանական վերլուծություն - Հախվերդյան, Նազելի (Արմավ հրատ.)
The psychological analysis of the story of “The Evil of Mtnadzor” by Bakunts allowed to prove how deep Bakunts’ affiliation is to his native land,where lives and creates an honest person who respects and preserves national traditions, with his unique psychology, to face or compel the unexpected reality under standing of adaptability. Психологический анализ рассказа Ак. Бакунца «Мистика» Мтнадзора»» доказал настолько глубоко Бакунц связан с его замечательной родной землей, где живет честный человек, который создает и сохраняет национальные традиции, с его уникальной психологией,чтобы противостоять или адаптироваться неожиданной новой действительности.
Keywords: Գրական վերլուծություն